Hobnail variant of papillary thyroid carcinoma: A case with an unusual presentation. Issue 8 (16th April 2017) - Lilo, Mohammed T.; Bishop, Justin A.; Ali, Syed Z.
Abstract: Variants of papillary thyroid carcinoma (PTC) account for up to 25% of the cases, some of which are proven to be associated with aggressive clinical behavior such as tall cell and columnar cell variants. Hobnail variant of PTC (HVPTC) is recently described as a rare and aggressive variant of PTC. Herein, we are reporting a case of HVPTC in a patient who presented with hemoptysis and an intratracheal blood clot that was aspirated and submitted for cytopathological examination. Cytomorphology displayed neoplastic cells with profound micropapillary architecture, elongated nuclei, and prominent hobnail configuration. Nuclear features of PTC such as pseudoinclusions, nuclear overlapping, crowding, and grooves were readily identified. Subsequent total thyroidectomy revealed a 1.4 cm PTC with columnar and hobnail components. HVPTC is a rare locally aggressive subtype, which may present with metastasis from an occult thyroid primary. HVPTC needs to be included in the differential diagnosis of metastatic carcinoma with micropapillary architecture on fine needle aspiration, particularly in head and neck area. Diagn. Cytopathol. 2017;45:754–756. © 2017 Wiley Periodicals, Inc.